2021
DOI: 10.1136/bmjopen-2020-042098
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for COVID-RV: a multicentre prospective observational cohort study of right ventricular dysfunction in ventilated patients with COVID-19

Abstract: IntroductionCOVID-19 can cause severe acute respiratory failure requiring management in intensive care unit with invasive ventilation and a 40% mortality rate. Cardiovascular manifestations are common and studies have shown an increase in right ventricular (RV) dysfunction associated with mortality. These studies, however, comprise heterogeneous patient groups with few requiring invasive ventilation. This study will investigate the prevalence and prognostic significance of RV dysfunction in ventilated patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
(23 reference statements)
0
15
0
2
Order By: Relevance
“…It is, indeed, well known that the quality of transthoracic echocardiographic images can be impaired by mechanical ventilation and suboptimal patient positioning in the ICU, as well as pulmonary disease itself [41]. Technical issues may be of particular concern for strain imaging, where the quality of images is essential for accurate strain tracking [42], which underlies the need of skilled and experienced echocardiographers to properly assess RV function in these complicated patients [43]. To summarize, there is now substantial evidence that RV dysfunction is a hallmark pathophysiological alteration associated with COVID-19, as extensively reviewed by Dandel [51].…”
Section: Right Ventricular Dysfunction In Covid-19: What Is the Evidence?mentioning
confidence: 99%
“…It is, indeed, well known that the quality of transthoracic echocardiographic images can be impaired by mechanical ventilation and suboptimal patient positioning in the ICU, as well as pulmonary disease itself [41]. Technical issues may be of particular concern for strain imaging, where the quality of images is essential for accurate strain tracking [42], which underlies the need of skilled and experienced echocardiographers to properly assess RV function in these complicated patients [43]. To summarize, there is now substantial evidence that RV dysfunction is a hallmark pathophysiological alteration associated with COVID-19, as extensively reviewed by Dandel [51].…”
Section: Right Ventricular Dysfunction In Covid-19: What Is the Evidence?mentioning
confidence: 99%
“…Zudem wurde in unserer Kohorte keine invasive Beatmung oder ECMO-Therapie durchgeführt. Beide gelten als Faktoren, die ansonsten insbesondere bei COVID-19-Patienten ebenfalls mit einer rechtsventrikulären Dysfunktion einhergehen [ 26 ].…”
Section: Diskussionunclassified
“…In unserer Kohorte zeigten sich die D‑Dimere nur gering erhöht (1,75 mg/l) und damit 4‑mal geringer als in schweren COVID-19 Fällen in HTx-Patienten (6,6 mg/dl) [ 16 ]. Zudem finden sich nach aktueller Datenlage thrombembolische Ereignisse in herztransplantierten Patienten vornehmlich in schweren COVID-19-Verläufen [ 26 ].…”
Section: Diskussionunclassified
“…Study protocol and methods have previously been reported [14]. We conducted a prospective, observational cohort study involving 10 ICUs in NHS Scotland.…”
Section: Study Design and Participantsmentioning
confidence: 99%